Prevalence and Correlates of Lifetime Alcohol Use among Adult Urban Populations in Iran: A Knowledge, Attitude, and Practice Study. Issue 3 (27th May 2019) - Mehrabi, Maryam; Hajebi, Ahmad; Mohebbi, Elham; Baneshi, Mohammad Reza; Khodadost, Mahmoud; Haghdoost, Ali Akbar; Sharifi, Hamid; Noroozi, Alireza
ABSTRACT: Globally, alcohol use is one of the leading contributors to the burden of disease. The aim of this study was to provide data on prevalence and correlates of lifetime alcohol use among Iranian adults living in urban areas. This cross-sectional study investigated knowledge, attitude, and practice (KAP) of Iranian adults towards drug and alcohol use. Participants were recruited from the capital cities of five provinces—Tehran, West Azerbaijan, Markazi, Kerman, and Khorasan Razavi—in 2015. We used multivariate logistic regression models to conduct data analysis. Completing the questionnaire were 2, 065 participants (44.06% female). Prevalence of lifetime alcohol use was 28% (95% CI: 25–29%). Lifetime alcohol use was significantly associated with male gender (Odds Ratio (OR) = 1.74, 95% Confidence Interval (CI): 1.26– 2.39), positive attitude towards alcohol (OR = 2.15, CI: 1.60–4.34), lifetime stimulants use (OR = 5.73, CI: 3.56– 9.23), and lifetime opioids use (OR = 4.47, CI: 3.12– 6.39). Estimated lifetime prevalence of alcohol use in our study was higher than the regional average. Primary alcohol prevention programs need to target sub- populations who are at risk for alcohol use and provide services that impede the development of positive attitudes towards alcohol.